Ultrasonographic Features of Hydatidiform Mole in a 35-Year-Old Woman Treated with Methotrexate: Imaging Findings and Drug-Induced Cutaneous Manifestations - Dria Anggraeny Sutikno (Sultan Agung Islamic University of Semarang, 2026)
Hydatidiform mole is a form of gestational trophoblastic disease (GTD) characterized by abnormal proliferation of trophoblastic tissue. It commonly presents with excessive uterine enlargement in early pregnancy and markedly elevated β-hCG levels. The spectrum of GTD comprises several pathologic entities, that originate from abnormal fertilization that leads to a proliferative process with similarities to the normal trophoblast. These entities include complete and partial hydatidiform moles, which constitutes more than 80% of cases; an invasive mole, which refers to persistent local disease after treatment; and choriocarcinoma, which constitutes 1% to 2% of cases. Early diagnosis and prompt management are crucial to prevent complications. This report describes a case of complete hydatidiform mole in a 35-years-old, in which diagnosis was primarily established through characteristic imaging findings, particularly on pelvic ultrasonography. The patient subsequently underwent methotrexate chemotherapy, with imaging also contributing to treatment monitoring and follow-up assessment. In addition, this report highlights the adverse effects of methotrexate, with particular emphasis on cutaneous manifestations.